2018
DOI: 10.1136/bmjopen-2017-020210
|View full text |Cite
|
Sign up to set email alerts
|

Do conceptualisations of health differ across social strata? A concept mapping study among lay people

Abstract: ObjectivesThe legitimacy of policies that aim at tackling socioeconomic inequalities in health can be challenged if they do not reflect the conceptualisations of health that are valued in all strata. Therefore, this study analyses how different socioeconomic groups formulate their own answers regarding: what does health mean to you?DesignConcept mapping procedures were performed in three groups that differ in educational level. All procedures followed exactly the same design.SettingArea of the city of Utrecht,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 17 publications
3
18
0
2
Order By: Relevance
“…Possible explanations for the perceived lack of connection between contextual factors and health might be related to the participants' biomedical and individually determined view of health or their notion that health is not in itself a consequence of context but actually a prerequisite for individuals to do other activities, for instance for working and studying. These health views have been previously described in other settings as well, even though there is important variation regarding countries, socioeconomic conditions, among other factors [73,74]. Thus, further analysis about these participants' views on health are considered relevant for health research and will be further elaborated and reported elsewhere.…”
Section: Discussionmentioning
confidence: 71%
“…Possible explanations for the perceived lack of connection between contextual factors and health might be related to the participants' biomedical and individually determined view of health or their notion that health is not in itself a consequence of context but actually a prerequisite for individuals to do other activities, for instance for working and studying. These health views have been previously described in other settings as well, even though there is important variation regarding countries, socioeconomic conditions, among other factors [73,74]. Thus, further analysis about these participants' views on health are considered relevant for health research and will be further elaborated and reported elsewhere.…”
Section: Discussionmentioning
confidence: 71%
“…Eleven articles were written from a context specific perspective. We divided these articles with a context specific perspective in four groups: cultural perspectives (4 articles) [ 75 78 ], immigrant perspectives (3 articles) [ 73 , 79 , 80 ], educational level perspectives (2 articles) [ 81 , 82 ], and other perspectives (2 articles) [ 83 , 84 ] (see Table 11 ). These contexts are diverse and cannot be seen as one similar group.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, a focus on possibilities, self-confidence, and acceptance were mentioned as supportive of good health. This indicates the importance of paying attention to the subjective dimensions that determine health judgements and the way in which citizens cope with circumstances [ 28 ]. The participants asked for different social activities in the community centers—e.g., a “Looking for sense” course nearby, in their own neighborhood and free of charge.…”
Section: Discussionmentioning
confidence: 99%
“…A prerequisite for citizen participation is to recognize how citizens perceive health and the issues that are important for them regarding health and wellbeing. Studies that explored low SES citizens' perceptions of health found that how people experience and define health differs depending on the context and the situation [28,29]. In general, citizens with a low SES are less likely to perceive the need for lifestyle advice and participate less often in lifestyle programs compared to citizens with a high SES [30][31][32].…”
Section: Introductionmentioning
confidence: 99%